Target Sign of Third Ventricle in Basilar Dolichoectasia with Multiple Clinical Presentations: A Case Report - Akshay S. Patil; Sandeep Iratwar; Chetan Rathod; Paresh Korde (Indian Journal of Neurosurgery)
Basilar dolichoectasia (BDE) is an uncommon anatomical variant usually detected incidentally or during stroke evaluation. BDE can occasionally become symptomatic and may present with stroke (infarct or hemorrhage), raised intracranial pressure due to obstructive hydrocephalus, or with cranial nerve palsies. We present a unique case of BDE presenting with obstructive hydrocephalus, stroke, and cranial nerve palsy in single patient and propose a radiological sign (target sign of third ventricle), which could aid in imaging diagnosis and further management.